Indonesian sugarcane crops have a variety of virus-carrying insects. What are their control methods? - Dahliani, Lili; Arshad, Imran; Usmiyatun, Usmiyatun (Revenue Journal: Management and Entrepreneurship, 2023)
This research identifies various types of insect vectors that are capable of spreading disease-causing viruses in sugarcane plants in Indonesia and explores methods of controlling them. The main vector insects are from the order Hemiptera, which have piercing and sucking type mouthparts. These insects play an important role in the spread of viruses such as sugarcane mosaic virus (SCMV), sugarcane streak mosaic virus (SCSMV), and sugarcane yellow leaf virus (SCYLV), which can cause significant deterrence in national sugarcane productivity. This research uses a qualitative modeling approach by reviewing the literature to collect data regarding methods of controlling virus vector insects. The research results show that insect vector control must be carried out in an integrated manner, prioritizing technical and biological control methods as well as routine monitoring. The use of insecticides is recommended only if the insect population increases significantly. These results provide practical guidance for reducing the negative impact of insect vectors on sugarcane productivity in Indonesia.